Counterion dependence on the synthetic viability of NHC-stabilized dichloroborenium cations - Muthaiah, Senthilkumar (2013)
The synthetic viability of several N-heterocyclic carbene stabilized dichloroborenium cations [NHC·BCl2]+ (NHC = (RC)2(NR′)2C; 1, R = R′ = Me; 2, R = H, R′ = iPr; 3, R = Me, R′ = iPr; 4, R = H, R′ = tBu; 5, R = H, R′ = 2,6-iPr2-C6H3) in the presence of Cl–, AlCl4–, OTf– (Tf = O2SCF3), NTf2–, and [BArCl4]− (ArCl = 3,5-Cl2-C6H3) was investigated. None of the target borocations could be synthesized in the presence of Cl–, as only neutral NHC·BCl3 compounds were observed. On the other hand, it was not surprising that all targeted cations were synthetically viable in the presence of AlCl4– but a different degree of interion interaction was evident from 11B NMR experiments. This was confirmed by X-ray analyses of [1·BCl2]+, [2·BCl2]+, and [3·BCl2]+ in the presence of AlCl4– counterions, as the degree of cation–anion interaction was dependent on the steric encumbrance of the corresponding NHCs. Apart from [4·BCl2]+, no borocation was synthetically viable when OTf– and NTf2– were used as the counterions. Finally, we were able to show that only [4·BCl2]+ could be synthetically viable without the counterion stabilization effect(s) as the preparation of [4·BCl2][BArCl4] was achieved. Even though the presence of [3·BCl2][BArCl4] was detected, this compound appeared not to be thermally stable, as it decomposed in solution after 48 h. The thermal stability of [4·BCl2]+ and instability of [3·BCl2]+ in the presence of [BArCl4]− was attributed to the presence and absence, respectively, of very weak intraion (agostic) interactions in these two borocations.